Customized "Whole-Cervical-Vertebral-Body" Reconstruction After Modified Subtotal Spondylectomy of C2-C7 Spinal Tumor Via Piezoelectric Surgery. Issue 6 (14th May 2019) - He, Shaohui; Yang, Xinghai; Yang, Jian; Ye, Chen; Liu, Weibo; Wei, Haifeng; Xiao, Jianru
Abstract: BACKGROUND: Radical resection is the first-line option in managing cervical primary chondrosarcoma. Favorable anterior reconstruction is challenging after multilevel total spondylectomy in the cervical spine. OBJECTIVE: To illustrate the application of piezoelectric surgery and three-dimensional (3D) printing techniques in spine surgery. METHODS: A 27-yr-old patient was referred to our center with complaints of nocturnal neck pain and right upper extremity weakness. A 2-stage radical tumor resection was conducted using piezoelectric surgery with pathologically tumor-free margins. A 3D-printed titanium microporous prosthesis (3D-PTMP) was designed to reconstruct the anterior column of the cervical spine between C1 and T1 for stability. RESULTS: The whole intraoperative blood loss was 2300 mL over the 2 procedures. The patient had an uneventful recovery, regaining ambulatory status 3 wk after the 2 operations without ventilator support or other severe complications. By the final 14-mo follow-up, the patient had achieved marked pain relief and favorable neurological improvement; a postoperative computed tomography scan indicated a good position of the 3D-printed construct between the endplates with no sign of tumor recurrence or implant subsidence. CONCLUSION: The applications of piezosurgery in total spondylectomy and in 3D-PTMP in reconstruction can be a favorable alternative for managing multilevel cervical spinal tumors. Further studies are warranted to validate this surgical strategy.